Zambian roses bloom - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
In a mere five years, Zambia has become the third largest African producer and exporter of cut flowers, catching up with the leaders Kenya and Zimbabwe. Currently 135 hectares are used for floriculture, principally occupied by more than 40 kinds of...